Analysis of Depletion and Inventory of the Fuel for the MNSR Research Reactor Using the Deterministic Code DRAGON5. (2nd April 2020) - Al Zain, Jamal; El Hajjaji, O.; El Bardouni, T.; Lahdour, M.
Abstract: The Syrian miniature neutron source reactor (MNSR), a 30-kW, 90.0% highly enriched uranium fueled (U-Al) MNSR-type reactor has gone critical. Under operating conditions of 2 h per day for 5 days a week at a peak thermal neutron flux of 1.0 × 10 12 n/cm 2 ·s, the estimated core life is 10 years. After the fuel is depleted, the full spent-fuel assembly will be replaced with new low-enriched uranium. This study presents the results of a multigroup fuel burnup and depletion analysis of the MNSR fuel lattice using the DRAGON5 transport lattice code. Furthermore, infinite multiplication factor k∞ and several two-group macroscopic parameters, including scattering cross section, fission cross section, total cross section, and diffusion coefficient, and the transport mean free path have been studied. In addition to this, fuel isotopic composition dependency on burnup was calculated as a part of this study. The results contained in this study can be used as a microscopic database for performing criticality safety analysis and shielding computations for the design of a spent-fuel storage cask for the MNSR reactor core.